PERANCANGAN JARINGAN ZERO LINK FAILURE PADA LAYER 2 - Samuel Aras Michael Aras Michael; Boy Yuliadi Yulisa Geni (Yayasan Pendidikan Cahaya Budaya Indonesia, 2026)
High network availability is a primary requirement in modern enterprise environments; however, disruptions caused by link failures often hinder operational continuity. This study aims to design a Layer 2 network using Spanning Tree Protocol (STP) and EtherChannel technologies to realize the concept of zero link failure, which ensures the network maintains connectivity automatically when a link failure occurs. The research method adopted is an experimental approach, using Cisco Packet Tracer as the testing medium and network traffic analysis with Wireshark. The research process follows the PPDIOO (Prepare, Plan, Design, Implement, Operate, Optimize) framework, beginning with network requirement analysis at PT. XYZ, topology design, and the simulation of STP and EtherChannel configurations to enhance redundancy and bandwidth capacity. The simulation results indicate that the network design is capable of maintaining connectivity even when one physical link fails, with a recovery time of less than 5 seconds. Additionally, it significantly improves network stability and throughput. The implementation of STP prevents loop occurrences, while EtherChannel aggregates multiple physical links into a single logical link, providing resilience against failure. Although limited to simulation, this research offers practical solutions to enhance the reliability of Layer 2 networks on an enterprise scale. Further testing on real hardware is recommended for validation and further development of future implementations.